The Use of Figurative Language in Survivor’s Album Eye of the Tiger: A Semiotic Analysis of Metaphor, Simile, and Hyperbole - Purnamawati, Ni Nyoman Ayu; Skolastika, I Made Perdana (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This study investigates the use of figurative language-specifically metaphor, simile, and hyperbole-in the lyrics of Survivor’s 1982 album Eye of the Tiger. Employing a qualitative semiotic approach, the research analyzes 25 instances of figurative language across nine songs. The findings reveal metaphors as the dominant figure of speech (48%), followed by similes (32%) and hyperboles (20%). These rhetorical devices collectively enhance the expression of resilience, empowerment, and adversity, deepening the emotional resonance with listeners. This study addresses a research gap by exploring how these devices interact within the album’s narrative rather than in isolation. The results demonstrate the essential role of figurative language in conveying complex cultural narratives in popular music.